Surface salt bridges contribute to the extreme thermal stability of an FN3‐like domain from a thermophilic bacterium. Issue 1 (11th October 2021) - Boucher, Lauren; Somani, Sandeep; Negron, Christopher; Ma, Wenting; Jacobs, Steven; Chan, Winnie; Malia, Thomas; Obmolova, Galina; Teplyakov, Alexey; Gilliland, Gary L.; Luo, Jinquan
Abstract: This study uses differential scanning calorimetry, X‐ray crystallography, and molecular dynamics simulations to investigate the structural basis for the high thermal stability (melting temperature 97.5°C) of a FN3‐like protein domain from thermophilic bacteria Thermoanaerobacter tengcongensis (FN3 tt ). FN3 tt adopts a typical FN3 fold with a three‐stranded beta sheet packing against a four‐stranded beta sheet. We identified three solvent exposed arginine residues (R23, R25, and R72), which stabilize the protein through salt bridge interactions with glutamic acid residues on adjacent strands. Alanine mutation of the three arginine residues reduced melting temperature by up to 22°C. Crystal structures of the wild type (WT) and a thermally destabilized (∆Tm −19.7°C) triple mutant (R23L/R25T/R72I) were found to be nearly identical, suggesting that the destabilization is due to interactions of the arginine residues. Molecular dynamics simulations showed that the salt bridge interactions in the WT were stable and provided a dynamical explanation for the cooperativity observed between R23 and R25 based on calorimetry measurements. In addition, folding free energy changes computed using free energy perturbation molecular dynamics simulations showed high correlation with melting temperature changes. This work is another example of surface salt bridges contributing to the enhanced thermal stability of thermophilic proteins. The molecular dynamics simulation methods employed in this study may be broadly useful for in silico surface charge engineering of proteins.